REVEALING THE CULTURE OF SYMBOLIC VIOLENCE IN LANGUAGE LEARNING PRACTICES: LEARNING FROM KI HADJAR DEWANTARA - Mohammad Andi Hakim; Syihabuddin . (IAIN Syekh Nurjati Cirebon, 2024)
This study investigates the phenomenon of symbolic violence within the framework of language learning. Pierre Boudieu's notion of symbolic violence exposes the exercise of linguistic authority and ideology in educational activities. The ideas, doctrines, religious rulings, and educational principles formulated by Ki Hadjar Dewantara are fundamentally opposed to views that reject the use of symbolic violence. This research employs a qualitative approach, specifically focusing on a literature study. The research data is derived from an analysis of the current state of symbolic violence in language learning methods, as well as Ki Hadjar's perspectives on education. The data analysis process had three main stages: firstly, comprehending the text inside the book under examination; secondly, recognising the presence of symbolic violence within the culture; and finally, developing the notion of child-friendly language teaching. The research findings demonstrate that the ideas of Ki Hadjar Dewantara can be effectively applied to challenge the culture of power and violence in language learning. Specifically, the concepts of Trisaksi Jiwa, Tri Nga, and the pamomong pattern have the potential to transform the culture of language learning that perpetuates symbolic violence